Porcine liver vascular bed in Biodur E20 corrosion casts - Eberlova, L; Liska, V; Mirka, H; Gregor, T; Tonar, Z; Palek, R; Skala, M; Bruha, J; Vycital, O; Kalusova, K; Haviar, S; Kralickova, M; et al. (Folia morphologica, 2016)
BACKGROUND: Pigs are frequently used as animal models in experimental medicine. To identify processes of vascular development or regression, vascular elements must be recognised and quantified in a three-dimensional (3D) arrangement. Vascular corrosion casts enable the creation of 3D replicas of vascular trees. The aim of our study was to identify suitable casting media and optimise the protocol for porcine liver vascular corrosion casting. MATERIALS AND METHODS: Mercox II® (Ladd Research, Williston, Vermont, USA) and Biodur E20® Plus (Biodur Products, Heidelberg, Germany) were tested in 4 porcine livers. The resins (volume approximately 700 mL) were injected via the portal vein. Corrosion casts were examined by macro-computed tomography, micro-computed tomography and scanning electron microscopy. RESULTS: For hepatectomies, the operating protocol was optimised to avoid gas or blood clot embolisation. We present a protocol for porcine liver vascular bed casting based on corrosion specimens prepared using Biodur E20® epoxy resin. CONCLUSIONS: Only Biodur E20®Plus appeared to be suitable for high-volume vascular corrosion casting due to its optimal permeability, sufficient processing time and minimum fragility. Biodur E20® Plus is slightly elastic, radio-opaque and alcohol-resistant. These properties make this acrylic resin suitable for not only vascular research but also teaching purposes.
Keywords: prasata; Swine; Capillaries; Corrosion Casting; Biodur E20; porcine liver; Corrosion; rentgenová mikrotomografie; vascular corrosion cast; micro-computed tomography; Animals; játra; Microscopy, Electron, Scanning; zvířata; X-Ray Microtomography; scanning electron microscopy; kapiláry; korozní odlévání; Liver; mikroskopie elektronová rastrovací; koroze